The Effect of Throwing and Catching Exercises on Basketball Playing Ability of Grade 3 Students at SDI Unggulan BTN Pemda - Arga Arga; Erniyanti Erniyanti (International Journal of Experimental Sports Science Research, 2025)
Background: Throwing and catching skills form the primary foundation of basketball that must be developed from an early age. For Grade 3 elementary students, hand-eye coordination, fine motor control, and ball-handling confidence are essential prerequisites in physical education learning. However, the lack of structured training programs targeting these fundamental skills hinders the improvement of basketball abilities at the elementary level. Objectives: This study aimed to analyze the effect of an 8-week structured throwing and catching training program on basketball playing ability among Grade 3 students at SDI Unggulan BTN Pemda. Methods: A pre-experimental one-group pre-test post-test design was applied to 30 Grade 3 students (15 male, 15 female) selected through total sampling. Instruments included chest pass accuracy test, bounce pass test, overhead pass test, zigzag dribbling, lay-up test, and a modified 3 vs 3 game assessment. The intervention was conducted 3 sessions per week for 8 weeks. Results: Significant improvements were found across all basketball playing ability variables (p < 0.05). The largest gains were in chest pass accuracy (+48.6%), followed by bounce pass (+41.2%) and 3 vs 3 game score (+38.4%). Significant improvements were also noted in zigzag dribbling (-24.8%), overhead pass (+36.7%), and lay-up (+33.1%). Conclusions: A systematic and structured throwing and catching training program significantly improved basketball playing ability among Grade 3 students at SDI Unggulan BTN Pemda, proving effective as a pedagogical approach in elementary school physical education.